Response of Meloidogyne javanica to Silver Nanoparticle Liquid from Agricultural Wastes - O. A. Fabiyi; A. O. Claudius-Cole; G. A. Olatunji; D. O. Abubakar; O. A. Adejumo (AGRIVITA, Journal of Agricultural Science, 2021)
Plant-parasitic nematodes attack is an important problem on crop production worldwide. Meloidogyne javanica is a potentially damaging pest of several crops. Laboratory studies were conducted to examine the effect of supernatant liquid from the synthesis of silver nanoparticles with agricultural wastes on the survival and hatching of Meloidogyne javanica juveniles and eggs. The experiment consisted of five treatments (carbofuran, corn cobs, rice husk, guinea corn chaff, and distilled water served as control) at three concentrations of 10, 20, and 30%. Each was repeated three times in a complete randomized design. Nematicidal bioassay revealed a consequential (p=0.05) decrease in egg hatch rate in 20 and 30% concentrations of the nanoparticle supernatant liquid. Similarly, percentage mortality increased significantly (p=0.05) in the nano supernatant liquid, with the corncob silver nanoparticle having the highest percentage mortality. These results confirmed that the agricultural waste silver nanoparticle supernatant liquid could be a cost-effective and eco-friendly nematicide.